1994
DOI: 10.1016/0014-5793(94)80203-3
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli PII protein: purification, crystallization and oligomeric structure

Abstract: The Escherichia coli signal transduction protein P,,, product of the glnB gene, was overproduced and purified. The predicted molecular weight of the protein based on the correct nucleotide sequence is 12,427 and is very close to the value 12.435 obtained by matrix-assisted laser desorption mass spectrometry. Hexagonal crystals of the unuridylylated form of P,, with dimensions 0.2 x 0.2 x 0.3 mm were grown and analysed by X-ray diffraction. The crystals belong to space group P6, with a = b = 6 1.6 A, c = 56.3 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
(6 reference statements)
2
20
0
Order By: Relevance
“…However, subsequent crystallization studies and sedimentation equilibrium experiments have shown that it is in fact a trimer (33,46,236). The molecular mass of the P II monomer was elucidated by matrix-assisted laser desorption mass spectrometry and shown to be 12,435 Da, which agrees very well with the prediction from the DNA sequence of 12,427 Da (235,236).…”
Section: Biochemistry Of P II Proteinssupporting
confidence: 71%
“…However, subsequent crystallization studies and sedimentation equilibrium experiments have shown that it is in fact a trimer (33,46,236). The molecular mass of the P II monomer was elucidated by matrix-assisted laser desorption mass spectrometry and shown to be 12,435 Da, which agrees very well with the prediction from the DNA sequence of 12,427 Da (235,236).…”
Section: Biochemistry Of P II Proteinssupporting
confidence: 71%
“…From results based on gel filtration (124) and combined native and SDS-polyacrylamide gel electrophoresis, it was concluded that GlnB consists of four identical subunits (149). However, after sedimentation equilibrium analysis (150) and preliminary X-ray diffraction analysis (150,151), it was concluded that GlnB was a homotrimer instead of a homotetramer. This was confirmed by resolving the structure of nonuridylylated GlnB at a high resolution through X-ray diffraction analyses (152,153).…”
Section: Glnbmentioning
confidence: 99%
“…coli strain RB9040 bearing plasmid pRJ1 or pRJ1 with appropriate single site mutations was used for production of wild-type PII and mutants. The production and purification of the proteins were essentially as described previously [11] with the exception that the cellfree extract obtained after French press lysis was treated with DNase (10 ~tg/ml) for 1 h at 37°C. Similarly, UT/UR produced by the direction of plasmid pNV101 was partially purified by ammonium sulfate precipitation followed by DEAE ion exchange chromatography.…”
Section: Purification Of Piimentioning
confidence: 99%
“…Previously we over-expressed PH and separated the unmodified PII from the uridylylated form [5,11]. In this work the expression of PII and mutants were carried out in E. coli strain RB9040 (UT/UR deficient strain) so that only unmodified PII was formed.…”
Section: Expression Of Pit and Mutantsmentioning
confidence: 99%
See 1 more Smart Citation